Effects of Resistance Band Exercise on Flexibility among Children Aged 6–7 Years: A Quasi-Experimental Study - Achzalay; Agung Cahya Karyadi (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2026)
Flexibility is an important component of physical fitness that supports children’s movement abilities. This study aimed to examine the effect of resistance band gymnastics on flexibility among children aged 6–7 years. A quantitative approach with a pretest–posttest control group design was employed. The participants consisted of 40 first-grade students divided into an experimental group and a control group, with 20 students in each group. The experimental group participated in a resistance band gymnastics program for 12 sessions conducted three times per week, whereas the control group followed regular physical education activities. Flexibility was measured using the sit-and-reach test. The experimental group’s mean score increased from −3.68 cm at pretest to 3.88 cm at posttest, representing an improvement of 7.56 cm. The control group’s mean score increased from 0.13 cm to 0.70 cm, representing an improvement of 0.57 cm. The results indicate that the experimental group experienced a greater improvement in sit-and-reach performance than the control group. Therefore, resistance band gymnastics may be used as an alternative activity to improve hamstring and lower-back flexibility among children aged 6–7 years.